Potential Significance of the Lymph Node Metastasis in Distal Gastric Cancer - 刘瑞廷; 王国荣; 车向明; 邱健; 王小强; 闫立昆; 李小军; 刘昌 (临床与病理杂志, 2026)
Objective: A retrospective study was conducted to investigate the rules of lymph node metastases in distal gastric cancer and its clinical significance. Methods: This study was performed on 129 patients who had distal gastric cancer with lymphadenectomy for radical cure, whose specimens were obtained during surgery. Results: Among 129 patients with distal gastric cancer, lymph node metastases were found in 80 patients (62.02%) with a total collection of 3,295 lymph nodes and an average of 25.54 lymph nodes per patient. Conclusion: According to the clinical and pathological factors and combining it with the characteristics of lymph node metastasis by groups and stations in different areas and then properly choosing and extending the extent of lymph node resection, the objective of radical cure for distal gastric cancer could be achieved individually when it is performed radical lymphadenectomy.